Novel insights into cancer stem cells targeting: CAR-T therapy and epigenetic drugs as new pillars in cancer treatment - Veschi, Veronica; Turdo, Alice; Stassi, Giorgio (Frontiers in Molecular Medicine, 2023)
Cancer stem cells (CSCs) represent the most aggressive subpopulation present in the tumor bulk retaining invasive capabilities, metastatic potential and high expression levels of drug efflux pumps responsible for therapy resistance. Cancer is still an incurable disease due to the inefficacy of standard regimens that spare this subpopulation. Selective targeting of CSCs is still an unmet need in cancer research field. Aberrant epigenetic reprogramming promotes the initiation and maintenance of CSCs, which are able to escape the immune system defense. Promising therapeutic approaches able to induce the selective inhibition of this stem-like small subset include immunotherapy alone or in combination with epigenetic compounds. These strategies are based on the specific expression of epitopes and/or epigenetic alterations present only in the CSC and not in the other cancer cells or normal cells. Thus, the combined approach utilizing CAR-T immunotherapy along with epigenetic probes may overcome the barriers of treatment ineffectiveness towards a more precision medicine approach in patients with known specific alterations of CSCs. In this perspective article we will shed new lights on the future applications of epi-immunotherapy in tumors enriched in CSCs, along with its potential side-effects, limitations and the development of therapy resistance.